Physical Characterization of Briquettes Composed of Corn Cob and Sawdust Waste Mixtures - Yusron, Rifky Maulana; Budiarto, Hairil; Irawan, Ibnu (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2024)
Corncobs were agricultural waste, while sawdust was waste of furniture industries.  Both materials can well decomposition naturally, but it was still time-consuming. The aim of this research to provide both wastes by converting them into sustainable and worthwhile solid-fuels briquettes format. In this research, variation of mixture ratio of corn cob powder and sawdust in briquettes used was 50:50, 60:40, 70:30, 80:20, and 90:10. 1:1 ratio of tapioca starch and water was used as the adhesive to bond the briquette mixture well. Compaction process used hydraulics by 2 tons pressing load. Testing of physical characteristics includes calorific value, moisture, and ash content. The lowest calorific value was 4589.94 kCal/g, which was achieved in the 50:50 mixture of corn cob and sawdust. The highest calorific value was 6579.87 kCal/g, which was achieved in the combination of a corn cob and sawdust ratio of 90:10. The calorific value continued to increase with more mixture of corn cob. Highest moisture content was 20.00%, achieved in 50:50 combination mixture of corn cob and sawdust. Moisture content decreased as the ratio of corn cobs used in the briquettes increased, with the lowest content obtained at 8.88% using a 90:10 mixture of corn cobs and sawdust. Highest ash content on this research 16.85%, was achieved in the 50:50 combination of corncob and sawdust. Ash content also tended to decrease with the increase of corn cob powder used in the briquettes. Lowest ash content was obtained at 10.10% using a mixture of corn cob and sawdust 90:10.